2022
DOI: 10.1111/tid.13885
|View full text |Cite
|
Sign up to set email alerts
|

Safety and value of pretransplant antibiotic allergy delabeling in a quaternary transplant center

Abstract: Background: Self-reported antibiotic allergies, also known as antibiotic allergy labels, are common and may lead to worse patient outcomes. Within immunocompromized patients, antibiotic allergy labels can lead to inappropriate use of antimicrobials and may limit options for prophylactic and therapeutic options in the posttransplant period.While antibiotic allergy delabeling is considered an important aspect of antibiotic stewardship protocols, evidence and awareness of its application in transplant recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Gorsline et al found that sulfa antibiotic delabeling of 11 SOT recipients resulted in an estimated $254–$2910 saved per patient. 50 …”
Section: New Challenge 2: Antibiotic Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Gorsline et al found that sulfa antibiotic delabeling of 11 SOT recipients resulted in an estimated $254–$2910 saved per patient. 50 …”
Section: New Challenge 2: Antibiotic Allergymentioning
confidence: 99%
“…Gorsline et al found that sulfa antibiotic delabeling of 11 SOT recipients resulted in an estimated $254-$2910 saved per patient. 50 Clinicians may administer validated questionnaires such as PEN-FAST to identify patients who can be delabeled outright and those who require allergy testing or desensitization. 43,44 Desensitization should be conducted pre-transplant, given the often fluctuating clinical status post-transplantation.…”
Section: New Challenge 1: Is Shorter (Antimicrobial Duration) Better?mentioning
confidence: 99%
“…Pretransplant antibiotic allergy evaluation has been successfully implemented at some centers leading to de-labeling of most reported allergies and increased use of preferred agents. [24][25][26] Therefore, detailed history taking and nuanced reporting on allergy is essential. Furthermore, the allergy guidelines have clarified the risk of cross-reactivity among beta-lactams is lower than previously suggested.…”
Section: F I G U R Ementioning
confidence: 99%
“…Beta‐lactam allergies are associated with increased use of second‐line, nonstandard antimicrobial agents. Pretransplant antibiotic allergy evaluation has been successfully implemented at some centers leading to de‐labeling of most reported allergies and increased use of preferred agents 24–26 . Therefore, detailed history taking and nuanced reporting on allergy is essential.…”
Section: Antibacterialsmentioning
confidence: 99%